Contrasting effects of organic materials versus their derived biochars on maize growth, soil properties and bacterial community in two type soils - Yue, Xiaosong; Liu, Xing; Wang, Fei; Shen, Changwei; Zhang, Ying (Frontiers in Microbiology, 2023)
The objective of this study was to assess the benefit of applying biochar instead of its feedstock in enhancing soil quality. To accomplish this, we investigated the short-term effects of two organic materials and their derived biochars on maize growth, soil properties, and microbial community in fluvo-aquic and red soil with a pot experiment. Five treatments were applied to each soil, namely, the addition of straw, manure, straw-derived biochar, manure-derived biochar, and the control with no addition of any organic materials and biochar. Our results revealed that straw decreased the shoot biomass of maize in both soils, while straw-derived biochar, manure and manure-derived biochar increased it by 51.50%, 35.47% and 74.95% in fluvo-aquic soil and by 36.38%, 117.57% and 67.05% in red soil compared with the control, respectively. Regarding soil properties, although all treatments increased soil total organic carbon, straw and manure exhibited more pronounced effects on improving permanganate-oxidizable carbon, basal respiration, and enzyme activity compared with their derived biochars. Manure and its biochar had more significant effects on improving soil available phosphorus, whereas straw and its biochar exhibited more ameliorating effects on available potassium. Straw and manure consistently decreased bacterial alpha diversity (Chao1 and Shannon index) and altered bacterial community composition in the two soils by increasing the relative abundances of Proteobacteria, Firmicutes, and Bacteroidota and decreasing those of Actinobacteriota, Chloroflexi, and Acidobacteriota. More specifically, straw had a greater effect on Proteobacteria, whereas manure affected Firmicutes more. While straw-derived biochar had no effect on bacterial diversity and bacterial community composition in both soils, manure-derived biochar increased bacterial diversity in the fluvo-aquic soil and altered bacterial community composition in the red soil by increasing the relative abundances of Proteobacteria and Bacteroidota and decreasing that of Firmicutes. In summary, owing to the input of active organic carbon, straw and manure exhibited more pronounced short-term effects on soil enzyme activity and bacterial community compared with their derived biochar. Furthermore, straw-derived biochar was found to be a better option than straw in promoting maize growth and nutrient resorption, while the choice of manure and its biochar should be determined by the soil type.